(untitled) (Fiep Bulletin - online, 2013)
This study aimed to investigate the acceptability of classes dealing on the subject of functional training for high school students during physical education classes at school. It also sought to understand infer the possibility of inclusion of the theme of functional training and its concepts as curriculum in physical education classes in high school. The sample was composed of students from a school of high school, a member of the State Department of Education of Rio de Janeiro. The methodology consisted of two stages, the first related to the application of lessons focusing on content related to functional training, specifically, strength, balance and aerobic endurance. The second phase dealt with the application of a questionnaire to collect data, with open and closed questions, which analyzed the lessons applied. Among the results, we have: 1) 50% of students rated the class as very good; 2) 80% of the students indicated that they learned something new in class, 3) 69% of students felt motivated to make the class. Consequently, the results of this study show that the inclusion of content related to functional training was well accepted by the student body of the school since enabled a reflection on the importance and benefits of physical activity, being then a possibility to use as curriculum content in school physical education classes in high school.